2021
DOI: 10.1093/noajnl/vdab086
|View full text |Cite
|
Sign up to set email alerts
|

Necessity for craniospinal irradiation of germinoma with positive cytology without spinal lesion on MR imaging—A controversy

Abstract: Background Cerebrospinal fluid (CSF) cytology and spinal MR imaging are routinely performed for staging before treatment of intracranial germinoma. However, the interpretation of the results of CSF cytology poses two unresolved clinical questions: 1) Does positive CSF cytology correlate with the presence of spinal lesion before treatment?; and 2) Is craniospinal irradiation (CSI) necessary for patients with positive CSF cytology in the absence of spinal lesion? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These dose-dependent structural changes might explain the mechanism behind the declines in intelligence and employment status observed in Group A patients. We have previously demonstrated that radiation volume and dose are positively associated with the number of microbleeds in germinoma patients [ 28 ]. Elucidation of the relationship between microbleeds and clinical symptoms and the significance of microbleeds for the prediction of neurological deterioration remains as a challenge for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dose-dependent structural changes might explain the mechanism behind the declines in intelligence and employment status observed in Group A patients. We have previously demonstrated that radiation volume and dose are positively associated with the number of microbleeds in germinoma patients [ 28 ]. Elucidation of the relationship between microbleeds and clinical symptoms and the significance of microbleeds for the prediction of neurological deterioration remains as a challenge for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation field was modified according to the distribution of the tumor. Patients with positive cerebrospinal fluid (CSF) cytology and/or spinal dissemination on magnetic resonance imaging (MRI) received 24 Gy of radiation therapy to the craniospinal axis [ 28 ], whereas patients with basal ganglia germinoma received 24 Gy to the whole brain.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, tumor cells are present in the spinal fluid in only 38% of germinomas (25/66), so positive cytology is not a dependable diagnostic test. 71 Furthermore, positive CSF cytology was not correlated with presence of spinal lesions on MRI. 71 Even as a prognostic test, cytology has limitations as non-cranio-spinal irradiation achieved excellent progression-free survival (PFS) even in patients with positive CSF cytology without spinal lesion on MRI.…”
Section: Diagnosismentioning
confidence: 94%
“… 71 Furthermore, positive CSF cytology was not correlated with presence of spinal lesions on MRI. 71 Even as a prognostic test, cytology has limitations as non-cranio-spinal irradiation achieved excellent progression-free survival (PFS) even in patients with positive CSF cytology without spinal lesion on MRI. Finally, CSF pleocytosis, presence of CSF oligoclonal bands, and abnormalities of CSF IgG can occur in germinoma, 40 , 55 so CSF suggestive of other disease processes, like multiple sclerosis, does not necessarily exclude germinoma.…”
Section: Diagnosismentioning
confidence: 94%
See 1 more Smart Citation